Inhibitory Effect of Iodoacetate on Developmental Competence of Porcine Early Stage Embryos In Vitro - NI WAYAN KURNIANI KARJA; MOKHAMAD FAHRUDIN; KAZUHIRO KIKUCHI (Bogor Agricultural University, Indonesia, 2009)
In porcine preimplantation embryos, glucose-utilizing pathways are reported active throughout their development. The aim of this study was to test the involvement of glycolysis activity in early stage of porcine embryo development by the addition of iodoacetate, a glycolytic inhibitor, to culture medium. In vitro matured and fertilized oocytes were cultured for the first 2 days in iodoacetate at concentrations of 0, 1, or 2.5 µM. The proportion of viable embryos on day 4 decreased when Ia was added at concentration of 2.5 µM (P < 0.05). The development of cleaved embryos to the blastocyst stage on day 6 was significantly reduced by 1 µM iodoacetate and none of cleaved embryos in Ia-2.5 group develop to the blasyocyst stage (P < 0.05). More than 60% of embryos in Ia-2.5 group were arrested at the two-four-cell stage, and then arrested at the morula stage. These results indicate that glucose plays important roles in supporting the development of early stage of porcine embryos and that the inhibition of glucose metabolism may disrupt the management of energy production, leaving the embryos incompetence to develop. Key words: iodoacetate, glucose, early stage embryos, in vitro culture